Construction of Horizontal Wells in Municipal Solid Waste using a Directional Drill - Ho, Pei-Yi Joy (University of Waterloo, 2007)
Horizontal directional drilling (HDD) has been employed in many situations including cable lines under rivers and rehabilitation of pipelines under buildings and busy traffic. Within the context of a municipal landfill site, a by-product of organic waste (leachate) accumulates within an established landfill. Leachate is a liquid produced from the wastes placed inside landfills and rain that percolates through the wastes and reacts with the products of decomposition. This thesis investigates the effectiveness of employing HDD techniques to extract leachate in the municipal landfill application.
Keywords: Landfill; Directional Drilling; Civil Engineering